2019
DOI: 10.1002/1878-0261.12607
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 downmodulation enhances antitumor effects of histone deacetylase inhibitors in retinoblastoma by augmenting oxidative stress‐mediated apoptosis

Abstract: hydroxamic acid; TXN2, thioredoxin-2; UHRF1, ubiquitin-like with PHD and RING finger domains 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
5
29
0
Order By: Relevance
“…[224] Depletion of ubiquitin-like with PHD and RING finger domains 1 reduces TRX2 and increases intracellular ROS in retinoblastoma cells. [225] Glioma nitric oxide synthase 2 induces the S-nitrosylation of TRX2 and mitochondrial caspase 3 in microglial cells, reducing their activity and promoting tumorigenesis.…”
Section: Trx1/2mentioning
confidence: 99%
“…[224] Depletion of ubiquitin-like with PHD and RING finger domains 1 reduces TRX2 and increases intracellular ROS in retinoblastoma cells. [225] Glioma nitric oxide synthase 2 induces the S-nitrosylation of TRX2 and mitochondrial caspase 3 in microglial cells, reducing their activity and promoting tumorigenesis.…”
Section: Trx1/2mentioning
confidence: 99%
“…Of note, UHRF1 protein expression is much higher in primary MM tumor and MM cells compared to normal hPBMCs, and with an unfavorable prognosis in MM. Knockdown of UHRF1 expression in cancer cells significantly suppressed cell growth, indicating that UHRF1 is essential for the progression of cancer [39]. Interestingly, normal cells (BaF 3 and normal hPBMCs) expressing low UHRF1 are insensitive to BBR in contrast to MM cells which supports that UHRF1 may be the target of BBR.…”
Section: Discussionmentioning
confidence: 87%
“…Another study showed increase in ROCKII protein level in NMDA-induced retinal neurotoxicity, and its inhibitor acted as neuroprotective agent by abolishing the increase in ROCKII level ( Kitaoka et al, 2004 ). Apart from this, UHRF1 , which encode a protein that regulates DNA and histone methylation, and NR1H4 (Nuclear Receptor Subfamily 1 Group H Member 4), which encode ligand-activated transcription factor, are also found to be linked with inflammation ( Fiorucci et al, 2010 ; Wang et al, 2018 ), oxidative stress ( Gai et al, 2017 ; J. K. Kim J. K. et al, 2020 ), and angiogenesis ( Guo and Mo, 2020 ). Interestingly, in the present study, NR1H4 was also found to be one of the targets of down-regulated miRNA identified in a plasma sample of NPDR cases and thus can act as a preferred candidate in studies concerned with identification of circulatory prognostic biomarker for DR.…”
Section: Discussionmentioning
confidence: 99%